Carcass quality of broilers fed with banana tuber meal enriched with Saccharomyces cerevisiae as a β-glucan fiber - Imam, Shokhirul; Suryadi, Ujang; Muqorrobin , Syukron Ali (Indonesian Journal Publisher, 2024)
The background of the study is that broilers have high levels of fat and cholesterol in the body, which reduces the quality of the carcass. One way to improve this is by adding feed additive β-glucan. This study aims to evaluate the addition of banana tuber flour containing Saccharomyces cerevisiae as a source of β-glucan fiber in feed on broiler carcass quality. The method used was a completely randomized design consisting of 5 treatments and 4 replications, each treatment unit contained 10 chickens, making a total of 200 chickens raised for 37 days. β-glucan in feed was given at levels of 0, 25, 50, 75, and 100 ppm. Drinking water was given ad libitum, while feed was given using manufactured feed. Treatment was given at the age of 16 to 37 days. Parameters measured included live weight and carcass, and percentage of carcass and ab-dominal fat. Data were analyzed using ANOVA. The results revealed that banana tuber flour enriched with Saccharomyces cerevisiae as β-glucan fiber in feed significantly (P<0.05) increased live weight and body weight, but did not have a significant effect (P>0.05) on carcass percentage and abdominal fat. In conclusion, banana tuber flour enriched with Saccharomyces cerevisiae as β-glucan fiber in feed can increase live weight and body weight of broilers best at a concentration of 25 ppm